Absent or occult pulmonary artery. Issue 2 (August 1984) - Presbitero, P; Bull, C; Haworth, S G; de Leval, M R
Abstract : Of 12 patients with angiographically absent pulmonary artery, 11 were investigated surgically. The previously occult pulmonary artery was found in 10 patients, in five of whom a vestige of an intrapericardial artery was present and in five the artery was patent only at the hilus, a gap existing between the main pulmonary artery and the hilar vessel, and no artery was found in one. All patients with an intrapericardial artery had right ventricular outflow tract obstruction and a ductus descending vertically from underneath the aortic arch. In those without an intrapericardial vessel the occult artery was on the side opposite the aortic arch, and there was evidence of a ductus coming from the innominate artery on the side of the interruption. The occult pulmonary artery, where identified at operation, was usually joined initially to the systemic circulation. Ultimately, continuity between the hilar and main pulmonary artery may be established surgically. Where no intrapericardial vessel exists, however, a conduit may be required to bridge the gap. It seems advisable to search for the occult artery as early in life as is feasible in the hope that providing a blood supply will ensure development of the vessel and normal lung growth.